2018
DOI: 10.2175/106143017x15131012152979
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Heavy Metals from Aqueous Solution by Bacteria Isolated from Contaminated Soil

Abstract: This study was carried out to analyze the heavy metals biosorption potential of bacteria isolated from soil contaminated with electroplating industrial effluents. Bacterial isolates were screened for their multi-metal biosorption potential against copper, nickel, lead, and chromium. Bacterial isolate CU4A showed the maximum uptake of copper, nickel, lead, and chromium in aqueous solution, with a biosorption efficiency of 87.16 %, 79.62%, 84.92%, and 68.12%, respectively. The bacterial strain CU4A was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Similar changes in the FTIR spectrum due to arsenic biosorption were reported by Cristobel (Christobel and Lipton 2015). Changes at 3411 cm -1 , 2929 cm -1 , 1239 cm -1 , 1052 cm -1 , and 617 cm -1 peak intensities are in line with other reports (Dhanwal et al 2018).…”
Section: Resultssupporting
confidence: 93%
“…Similar changes in the FTIR spectrum due to arsenic biosorption were reported by Cristobel (Christobel and Lipton 2015). Changes at 3411 cm -1 , 2929 cm -1 , 1239 cm -1 , 1052 cm -1 , and 617 cm -1 peak intensities are in line with other reports (Dhanwal et al 2018).…”
Section: Resultssupporting
confidence: 93%
“…8 Analysis with SEM and EDX in previous studies confirmed the adsorption of metals on the bacterial biomass. For instance, SEM images of Gram-positive bacteria Bacillus cereus FIT10 (Dhanwal et al,2018) and Staphylococcus hominis strain AMB-2 (Rahman et al,2019) showed clear adsorption of Pb after heavy metals treatment. Moreover, EDX analysis also confirmed the presence of a Pb signal on the bacterial surface.…”
Section: Scanning Electron Microscopy (Sem) and Energy Dispersive X-r...mentioning
confidence: 99%
“…Bacteria were cultured as previously described. 20,21 Briey, single bacterial colony was inoculated in 3-5 ml of Luria-Bertani (LB) medium, followed by shaking overnight at 37 C at 220 rpm. Cell suspension was inoculated in LB medium at a ratio of 1 : 50, followed by shaking at 220 rpm at 37 C for 12-18 hours.…”
Section: Bacteria Cultivationmentioning
confidence: 99%
“…Chemical groups such as hydroxyl, carboxyl, amine and halide on bacterial surface are involved in adsorption and deposition of heavy metal ions as well as morphogenesis of biominerals. [19][20][21][22][23] It inspired researchers in using bacterial-mediated mineralization for synthesizing materials with applications in ecological restoration, sewage treatment, drug carrier, etc. [24][25][26] Factors such as temperature, pH, ion strength, biological templates and regulators have been extensively explored in biomineralization.…”
Section: Introductionmentioning
confidence: 99%